On the homology of the shoulder girdle in turtles. Issue 3 (23rd July 2014) - Nagashima, Hiroshi; Sugahara, Fumiaki; Takechi, Masaki; Sato, Noboru; Kuratani, Shigeru
ABSTRACT: The shoulder girdle in turtles is encapsulated in the shell and has a triradiate morphology. Due to its unique configuration among amniotes, many theories have been proposed about the skeletal identities of the projections for the past two centuries. Although the dorsal ramus represents the scapular blade, the ventral two rami remain uncertain. In particular, the ventrorostral process has been compared to a clavicle, an acromion, and a procoracoid based on its morphology, its connectivity to the rest of the skeleton and to muscles, as well as with its ossification center, cell lineage, and gene expression. In making these comparisons, the shoulder girdle skeleton of anurans has often been used as a reference. This review traces the history of the debate on the homology of the shoulder girdle in turtles. And based on the integrative aspects of developmental biology, comparative morphology, and paleontology, we suggest acromion and procoracoid identities for the two ventral processes. J. Exp. Zool. (Mol. Dev. Evol.) 324B: 244–254, 2015 . © 2014 Wiley Periodicals, Inc.